A hypoxia risk score for prognosis prediction and tumor microenvironment in adrenocortical carcinoma - Deng, Yuanyuan; Li, Huihuang; Fu, Jinglan; Pu, Ying; Zhang, Ying; Chen, Shijing; Tong, Shiyu; Liu, Huixia (Frontiers in Genetics, 2022)
Abstract Background: Adrenocortical carcinoma (ACC) is a rare malignant endocrine tumor derived from the adrenal cortex. Because of its highly aggressive nature, the prognosis of patients with ACC is not impressive. Hypoxia exists in the vast majority of solid tumors and contributes to invasion, metastasis, and drug resistance. This study aimed to reveal the role of hypoxia in ACC and develop a hypoxia risk score (HRS) for ACC prognostic prediction. Methods: Hypoxia-related genes were obtained from the Molecular Signatures Database. The training cohorts of patients with ACC were downloaded from The Cancer Genome Atlas, while another three validation cohorts with comprehensive survival data were collected from the Gene Expression Omnibus. In addition, we constructed a hypoxia classifier using a random survival forest model. Moreover, we explored the relationship between the HRS and immunophenotype in ACC to evaluate the efficacy of immune check inhibitors (ICI) therapy and prognosis of patients. Results: HRS and tumor stage were identified as independent prognostic factors. HRS was negatively correlated with immune cycle activity, immune cell infiltration, and the T-cell inflammatory score. Therefore, we considered the low HRS group as the inflammatory immunophenotype, whereas the high HRS group was a non-inflammatory immunophenotype. In addition, the HRS was negatively related to the expression of common immune checkpoint molecules such as CD274, CD200, CTLA-4, and TIGIT, suggesting that patients with a lower HRS respond better to immunotherapy. Conclusions: We developed and validated a novel HRS to predict the immunophenotype and response of patients with ACC to ICI therapy. These findings not only provide fresh prognostic indicators for ACC but also offer several promising treatment targets for this disease.